2022
DOI: 10.1111/jppi.12403
|View full text |Cite
|
Sign up to set email alerts
|

Research and training priorities of staff supporting individuals with intellectual disabilities with or without autism

Abstract: Research and training priority setting can help to direct limited resources to areas, which will have maximum benefit in improving the skills and knowledge of support workers to better meet the needs of their clients. Staff from a multi‐site organisation in Singapore that supports individuals with intellectual disability and/or autism completed a questionnaire identifying their research and training practices and priorities. Staff were asked to identify their access to training and research, and what they view… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…This suggests the need to provide training to support staff in facilitating functional communication in adults with severe/profound intellectual disability. Indeed, training is known to have positive impacts on changing staff behaviour to better support their clients (Knotter et al, 2018; Simpson et al, 2022). It is also necessary to ensure that any intervention implemented to facilitate functional communication for these adults is socially valid as even though it is effective, it may not be considered appropriate by those who are implementing it (Carter, 2010; Gormley et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests the need to provide training to support staff in facilitating functional communication in adults with severe/profound intellectual disability. Indeed, training is known to have positive impacts on changing staff behaviour to better support their clients (Knotter et al, 2018; Simpson et al, 2022). It is also necessary to ensure that any intervention implemented to facilitate functional communication for these adults is socially valid as even though it is effective, it may not be considered appropriate by those who are implementing it (Carter, 2010; Gormley et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The social interaction that occurs when people analyse phenomena and solve things together, is an important learning aspect of improvement work (Norman, 2015). Skills development for staff who support individuals with intellectual disabilities is promoted by multiple components such as workshops, coaching and feedback (Simpson et al, 2022), which build up the current improvement programme.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Simpson et al ( 2022 ), it was noticed that caregivers expressed an ardent desire for knowledge and training in this area. The research findings of Simpson et al ( 2022 ) further indicate that the training priorities identified by caregivers include the management of problematic behaviour, knowledge and understanding of ID, and practical interventions that encompass positive support in caregiving. These studies highlight the importance of providing caregivers with education and training to enhance their understanding of ID and equip them with effective strategies for caregiving.…”
Section: Discussionmentioning
confidence: 99%
“…Caregivers need to have a clear understanding of ID as it directly contributes to their ability to effectively cope with the challenges associated with caring for individuals with ID (Ezeonu et al 2021). In a study conducted by Simpson et al (2022), it was noticed that caregivers expressed an ardent desire for knowledge and training in this area. The research findings of Simpson et al (2022) further indicate that the training priorities identified by caregivers include the management of problematic behaviour, knowledge and understanding of ID, and practical interventions that encompass positive support in caregiving.…”
Section: Equipped After Trainingmentioning
confidence: 99%